2015
DOI: 10.1038/ncomms8487
|View full text |Cite
|
Sign up to set email alerts
|

Early emergence of Yersinia pestis as a severe respiratory pathogen

Abstract: Yersinia pestis causes the fatal respiratory disease pneumonic plague. Y. pestis recently evolved from the gastrointestinal pathogen Y. pseudotuberculosis; however, it is not known at what point Y. pestis gained the ability to induce a fulminant pneumonia. Here we show that the acquisition of a single gene encoding the protease Pla was sufficient for the most ancestral, deeply rooted strains of Y. pestis to cause pneumonic plague, indicating that Y. pestis was primed to infect the lungs at a very early stage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 63 publications
(107 reference statements)
3
78
1
Order By: Relevance
“…Another example of molecular adaptation is found in Pla. In a recent study, Zimbler et al showed that a singleamino-acid modification within Pla (I259T), which is found in modern Y. pestis strains, enhances the invasive capacity of Y. pestis during bubonic plague (55). Thus, it appears that the plasticity of the omptin active site contributes to the ability of omptins to cleave the different substrates that their host bacteria encounter.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of molecular adaptation is found in Pla. In a recent study, Zimbler et al showed that a singleamino-acid modification within Pla (I259T), which is found in modern Y. pestis strains, enhances the invasive capacity of Y. pestis during bubonic plague (55). Thus, it appears that the plasticity of the omptin active site contributes to the ability of omptins to cleave the different substrates that their host bacteria encounter.…”
Section: Discussionmentioning
confidence: 99%
“…Since these strains had acquired the virulence factor Pla, required for bacterial survival and extensive multiplication in and subsequent dissemination from lymph nodes (70), the disease may have been a severe, disseminated form of food-and waterborne yersiniosis. Alternatively, the acquisition of pla would also have enabled pneumonic plague and direct human-to-human transmission via the aerosol route (71,72). It is unlikely that these strains were maintained primarily by flea-borne transmission cycles.…”
Section: Retracing the Evolutionary History Of Y Pestismentioning
confidence: 99%
“…However, some transmission by fleabite might have occurred, because the early transmission potential that fleas have immediately after an infectious blood meal does not require ymt (73) or biofilm production (74). Modification of Pla function by an I259T substitution in modern pandemic Y. pestis strains has been hypothesized to have been important or even required for bubonic plague pathogenesis (6,72,75). However, some presentday Y. pestis strains still have the ancestral version of Pla and cause bubonic plague from a subcutaneous injection route, at least in rodents.…”
Section: Retracing the Evolutionary History Of Y Pestismentioning
confidence: 99%
“…Previous work has shown that the protease activity of Pla is necessary for the rapid proliferation of Y. pestis within the small airways of the lungs during pneumonic plague (34,35). As Y. pestis infection is generally extracellular in nature, it is therefore likely that Pla cleaves host targets within the alveolar space to alter innate immune responses within the lungs and to allow for rapid bacterial replication.…”
Section: Identification Of Pla Substrates Within Mouse Balfmentioning
confidence: 99%
“…One of the virulence factors of Y. pestis responsible for acute pathogenesis in mammals is the omptin family outer membrane protease Pla, which has a wide range of proteolytic, adhesive, and invasive properties (34)(35)(36)(37). The protease activity of Pla is essential for the development of pneumonic plague, and its best-studied activity in vitro is the activation of host plasminogen (plg) into plasmin (38)(39)(40).…”
mentioning
confidence: 99%